NUMERICAL AND EXPERIMENTAL INVESTIGATION OF A DOUBLE-PIPE HEAT EXCHANGER WITH SiO2 NANO-ADDITIVES - Selimefendigil, Fatih; Sirin, Ceylin; Öztop, Hakan Fehmi (Begell House Inc, 2022)
In this work, numerical and experimental analyses of a double-pipe heat exchanger with SiO2 nanoparticles were performed. The numerical study was conducted by using the k-e turbulence model with the Galerkin weighted residual finite element method. The nanofluid was used in the inner pipe at various solid particle volume fractions. Effects of flow rate and temperature on the overall heat transfer coefficient were examined. The Brownian motion effect was included in the effective thermal conductivity of the nanofluid. It was observed that the overall heat transfer coefficient enhanced with the inclusion of nanoparticle and increasing the volumetric flow rate of nanofluid. Even though the validation of the experimental study was conducted, there are discrepancies between the numerical and experimental studies which become higher for a higher mass flow rate. The deviations are 4.60% and 27.50% at volumetric flow rates of 0.87 L/min and 2.15 L/min.
Keywords: nanofluid; SiO2; heat exchanger; finite element method; 3D turbulent